Cervical Artery Dissections: Etiopathogenesis and Management - Keser Z; Chiang CC; Benson JC; Pezzini A; Lanzino G (Vascular Health and Risk Management, 2022)
Zafer Keser,1 Chia-Chun Chiang,1 John C Benson,2 Alessandro Pezzini,3 Giuseppe Lanzino4 1Department of Neurology, Mayo Clinic, Rochester, MN, USA; 2Department of Radiology, Mayo Clinic, Rochester, MN, USA; 3Department of Clinical and Experimental Sciences, Neurology Clinic, University of Brescia, Brescia, Italy; 4Department of Neurosurgery, Mayo Clinic, Rochester, MN, USACorrespondence: Zafer Keser, Department of Neurology – Mayo Clinic, 200 First St SW, Rochester, MN, 55905, USA, Email keser.zafer@mayo.eduAbstract: Cervical Artery Dissection (CeAD) is a frequent stroke etiology for patients younger than 50 years old. The most common immediate complications related to CeAD are headache and neck pain (65– 95%), TIA/ischemic stroke (> 50%), and partial Horner’s syndrome (25%). The prevailing hypothesis regarding the pathogenesis of sCeAD is that the underlying constitutional vessel wall weakness of patients with sCeAD is genetically determined and that environmental factors could act as triggers. The stroke prevention treatment of CeAD remains controversial, involving anticoagulation or antiplatelet therapy and potentially emergent stenting and/or thrombectomy or angioplasty for selected cases of carotid artery dissection with occlusion. The treatment of headache associated with CeAD depends on the headache phenotype and comorbidities. Radiographically, more than 75% of CeAD cases present with occlusion or non-occlusive stenosis. Many patients demonstrate partial and complete healing, more commonly in the carotid arteries. One-fifth of the patients develop dissecting pseudoaneurysm, but this is a benign clinical entity with an extremely low rupture and stroke recurrence risk. Good recovery is achieved in many CeAD cases, and mortality remains low. Family history of CeAD, connective tissue disorders like Ehlers-Danlos syndrome type IV, and fibromuscular dysplasia are risk factors for recurrent CeAD, which can occur in 3– 9% of the cases. This review serves as a comprehensive, updated overview of CeAD, emphasizing etiopathogenesis and management.Keywords: cervical artery dissection, genetics, stroke